中高齢者女性における転倒リスク認識と外出活動との関連 - 中村, 智子; 八田, 武俊; 八田, 武志; 藤原, 和美; 永原, 直子; 八田, 純子; 堀田, 千絵; 岩原, 昭彦; 伊藤, 恵美 (Journal of human environmental studies, 2017)
The aim of the present study was to clarify the factorial structure influencing risk awareness by focusing on how fall risk awareness affects activities and behavior in the daily lives of middle-aged and elderly women who often experience falls both indoors and outdoors. A 'fall risk awareness' checklist created by the authors in 2013 was used to assess risk awareness. The subject sample comprised 120 women (mean age 61.19 years) who underwent a regional health check in Y Hokkaido. The subject were divided into two groups according to the degree of risk awareness (a high risk awareness group and low risk awareness group) and examined using t-test to assess cognitive function, mobility, physical condition and degree of fall risk awareness. The relationship between fall risk awareness and each measurement item was analysed using Pearson's correlation coefficient. Furthermore, the interrelationship between fall risk awareness and physical condition, cognitive function, mobility and falls was found by covariance structure analysis. Pain associated with motor function affected reduced cognitive function and mobility. The results showed that reduced cognitive function affected by pain led to heightened awareness of risks. Higher risk awareness influenced by these factors increased the number of falls and decreased the frequency of outings. Even if subject had no problems with activities of daily living, encouraging the prevention of reduced cognitive function in the high risk awareness, while managing pain and preventing reduced mobility in the event of locomotor apparatus pain, can prevent falls and enable the maintenance of social activities such as outings.